Electrochemistry for Space Life Support. (March 2020) - Nelson, George J.; Vijapur, Santosh H.; Hall, Timothy D.; Brown, Brittany R.; Peña-Duarte, Armando; Cabrera, Carlos R.
Abstract : Electrochemical technology plays a key role in maintaining habitable environments for human space exploration. Historically, oxygen generation through electrolysis has been a key electrochemical technology for space life support. However, emerging electrochemical technologies are changing the way we process carbon dioxide and urine to supply oxygen and fresh water. Similarly, electrochemical production of hydrogen peroxide can support in-situ resource utilization to produce disinfectants for sanitary needs. These technologies will support space exploration that relies upon closed loop living and is increasingly independent of ground support, opening opportunities for human exploration of the Moon and Mars.